Investigation of the Antioxidant and Antimicrobial Properties of Ultrasound-Assisted Extracted Phenolics from Aronia melanocarpa Pomace - Iuliana Aprodu; Carmen Lidia Chitescu; Leontina Grigore-Gurgu; Loredana Dumitrașcu (Applied Sciences)
Black chokeberry (Aronia melanocarpa; BC) pomace represents an excellent source of compounds with health-promoting properties. This study investigated the contribution of ultrasound treatment to the recovery of phenolic compounds in comparison with conventional extraction, using water and ethanol solvents. The ultrasound amplitude was tested between 20% and 60%, for 10 min, with the highest concentrations of total polyphenols and antioxidant activity being measured at a 30% amplitude. Ultrasound treatment was able to reduce the extraction time for the efficient recovery of antioxidants, from 24 h as required in conventional extraction to several minutes while using lower amplitudes. Regardless of the ultrasound extraction conditions, the ethanolic extracts provided higher content of antioxidants compared to water extracts. The chromatographic analysis highlighted the presence of 48 bioactive compounds, including phenolic acids, isoflavones, flavones, flavanones, proanthocyanidins, flavonols and terpenes. BC extracts showed potential to inhibit the growth of Escherichia coli and Staphylococcus aureus. In addition, the potential mechanism associated with the antibacterial activity was revealed after performing molecular docking tests involving, as receptors, essential proteins for the survival and colonization functions of E. coli and S. aureus.